2010
DOI: 10.1039/c0sc00159g
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous generation and patterning of chiral polymeric surface toroids

Abstract: A chiral poly(n-hexyl isocyanate) can form ordered mesoscale toroidal structures when drop-cast on a variety of surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…[65] Again depending on an external input signal (light or heat) distinct product stereoisomers are accessible with as ingle (responsive) catalyst. Bringing the principle of switchable chiral catalysts in the realm of transition metal catalysis opens many new avenues including multitasking and cascade transformations,a daptive and responsive behavior and ultimately up/down-regulation of catalytic activity in complex catalytic networks.I ts hould be noted that dynamic control of function is not limited to catalysis as we demonstrated for instance in modulation of spin-spin interactions, [66] fluorescence, [67] gel [68] and amyloid fiber formation, [69] chiral recognition, and phosphate binding. [70] Ther ecent demonstration of intramolecular cargo transport [70] and av ariety of other mechanical tasks elegantly shown by the Sauvage, Stoddart, Leigh, Guiseppone,H arada and Aida groups and others,i llustrate the potential of molecular machine-like functions.…”
Section: Nobel Lectures Dynamic Control Of Functionmentioning
confidence: 85%
“…[65] Again depending on an external input signal (light or heat) distinct product stereoisomers are accessible with as ingle (responsive) catalyst. Bringing the principle of switchable chiral catalysts in the realm of transition metal catalysis opens many new avenues including multitasking and cascade transformations,a daptive and responsive behavior and ultimately up/down-regulation of catalytic activity in complex catalytic networks.I ts hould be noted that dynamic control of function is not limited to catalysis as we demonstrated for instance in modulation of spin-spin interactions, [66] fluorescence, [67] gel [68] and amyloid fiber formation, [69] chiral recognition, and phosphate binding. [70] Ther ecent demonstration of intramolecular cargo transport [70] and av ariety of other mechanical tasks elegantly shown by the Sauvage, Stoddart, Leigh, Guiseppone,H arada and Aida groups and others,i llustrate the potential of molecular machine-like functions.…”
Section: Nobel Lectures Dynamic Control Of Functionmentioning
confidence: 85%
“…Feringa et al demonstrated that poly(n-hexyl isocyanate) (PHIC) can self-assemble into long-range ordered toroids on mica when the solvent is evaporated (Figure 3c). [66] The AFM observations reveal a wide range of spatially aligned toroids with a d toroid of ≈150 nm and a D toroid ranging from 0.5 to 1.0 µm (Figure 3d). It was shown that the pattern possesses a high degree of long-range order with a periodic spacing of ≈2-6 µm.…”
Section: Self-assembly Of Synthetic Polymers Into Toroidal Nanostructuresmentioning
confidence: 98%
“…In addition to solution self-assembly, toroidal nanostructures can also be produced through evaporation-induced self-assembly of polymers. [57][58][59][60][61][62][63][64][65][66] Generally, the formation of toroids is induced by nucleation at defect sites or impurities during the evaporation of the solution. For example, Fujiki et al reported that poly(9,9di-n-decylfluorene) (PF10) self-assembled into toroids on mica surfaces when the chloroform solvent saturated with water was evaporated (Figure 3a).…”
Section: Self-assembly Of Synthetic Polymers Into Toroidal Nanostructuresmentioning
confidence: 99%
“…A recurring challenge in materials science involves developing methods to functionalize the surface of a material with a particular molecular or macromolecular structure . Applications include controlling surface energy and wettability , adhesion , chirality , sensors , the construction of molecular memory devices and surface‐attached molecular machinery . Control of surface functionality with thin polymer films affords many advantages including the ease with which films can be processed and the flexibility of the surface‐bound chains.…”
Section: Introductionmentioning
confidence: 99%